Factors Influencing English Language Learning in the Rural Malagasy Context: A Case Study of the Ambohidratrimo and Atsimondrano Districts - Andrianjary Myriam; Andrianarimanana Jean Claude Omer; Rakotoson Olivia; Razanadrasoa Vololonome Bodomalala; Koto-Te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Matondang Journal, 2023)
Qualified as an international language of communication and development, English is used worldwide and is essential for a country's development. This subject is taught in Malagasy public institutions from the sixth grade and is more advanced in private schools. Rural contexts, which are sometimes complicated and relatively weaker, compared to urban areas, in terms of technology and didactic materials, have an impact on the adoption of this language. The scarcity of linguistic immersion is among the challenges that rural education must face. A number of written questionnaires and oral interviews have been addressed to the target population, such as rural students, English teachers in public and private high schools, parents of students, and educational leaders or advisors. The XLSTAT statistical software was used to derive results that affirm the need to consider the contexts of English teaching and learning in rural areas, as well as the impacts of the linguistic environment. This requires the adoption of modeling, new approaches, and methods.